Implementation of Aceh Qanun Number 11 of 2018 in Southeast Aceh Regency Perspective Maṣlaḥah Al-Mursalah - Afri Hasni Putra; Tri Rasyid Desky; Fitra Jaya; Geri Suherman (Fox Justi : Jurnal Ilmu Hukum, 2025)
Study This For describe implementation related Aceh Qanun Regulation Number 11 of 2018 concerning institution Islamic finance in frame study implementation of qanun in perspective maṣlaḥah For explore and prove benefit of the qanun. Methodology study This use the approach used is approach juridical sociological, where in context law is effort understand something reality with look at the law as formal legal rules that are still in effect in form nas or those who have become product thinking man from results understanding to nas Good in the form of jurisprudence and laws. Primary data sources is through the interview process with subject study through technical sampling. While secondary data is covering from documents obtained from sources library consisting of from books, journals, research related to Aceh qanun institutions Islamic finance and concepts maṣlaḥah. Research results show that part public feel maṣlaḥah or the benefits from this qanun, while There is some of it Again Not yet feel benefits and knowledge about implementation of institutional regulations Islamic finance.